A hybrid fake banknote detection model using OCR, face recognition and hough features - Zarin, Adiba; Tasnim, Ummay; Jahan, Israt (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.